Fatigue and Fracture Testing of Weldments 1990
DOI: 10.1520/stp24094s
|View full text |Cite
|
Sign up to set email alerts
|

Study of Methods for CTOD Testing of Weldments

Abstract: Several precracking methods for crack-tip opening displacement (CTOD) testing of weldments were studied, including as local precompression, reverse bending, and high R-ratio fatigue. The precracking procedure could influence the validity of the precrack shape. However, it was found that an irregular precrack front had little effect on CTOD values of the heat-affected zone (HAZ). Results indicate that the current limitations on the fatigue precrack shape can be relaxed. CTOD values comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In addition, this kind of analysis might allow to determine whether the crack grew inter/intragranular, phase or microconstituent [67,73,74]. Regarding the sectioning technique in weldments samples, consult the following references [12,67,72,75,76]. Additional microstructural technique such as electron backscattered diffraction (EBSD) analysis could be used to determine the orientation of the grains where the crack grew [74,[77][78][79], in addition, whether other deformation mechanism was activate such as twinning [80].…”
Section: Fracture Surface Analysismentioning
confidence: 99%
“…In addition, this kind of analysis might allow to determine whether the crack grew inter/intragranular, phase or microconstituent [67,73,74]. Regarding the sectioning technique in weldments samples, consult the following references [12,67,72,75,76]. Additional microstructural technique such as electron backscattered diffraction (EBSD) analysis could be used to determine the orientation of the grains where the crack grew [74,[77][78][79], in addition, whether other deformation mechanism was activate such as twinning [80].…”
Section: Fracture Surface Analysismentioning
confidence: 99%
“…The cross-sections of the welded joints were polished and etched (3% nital) to reveal the microstructures. 9 Previously performed fracture toughness testing 10,11 showed that in the case of unstable crack propagation, the fracture toughness value depends on the microstructure of the crack tip region. Hence, fracture toughness analysis of unstable crack propagation requires classification of the fracture toughness data relating to the microstructures at the crack tip.…”
Section: Metallographic Investigation Of Microstructuresmentioning
confidence: 99%